Cover. Issue 10 (30th October 2019) - Vondrak, Karel; Parisi, Francesco; Dhawan, Anil; Grenda, Ryszard; Webb, Nicholas J. A.; Marks, Stephen D.; Debray, Dominique; Holt, Richard C. L.; Lachaux, Alain; Kelly, Deirdre; Kazeem, Gbenga; Undre, Nasrullah
Abstract : The cover image is based on the Original Article* Efficacy and safety of tacrolimus in de novo pediatric transplant recipients randomized to receive immediate‐ or prolonged‐release tacrolimus by Karel Vondrak & Nasrullah Undre** et al., https://doi.org/10.1111/ctr.13698 .***